Pathogenic Insights into DNA Mismatch Repair (MMR) Genes–Proteins and Microsatellite Instability: Focus on Adrenocortical Carcinoma and Beyond - Carsote, Mara; Turturea, Ionut Florin; Turturea, Maria Roxana; Valea, Ana; Nistor, Claudiu; Gheorghisan-Galateanu, Ancuta-Augustina (Diagnostics (Basel), 2023)
DNA damage repair pathways, including mismatch repair (MMR) genes, are prone to carcinoma development in certain patients. The assessment of the MMR system is widely recognized as part of strategies concerning solid tumors (defective MMR cancers), especially MMR proteins (through immunohistochemistry), and molecular assays for microsatellite instability (MSI). We aim to highlight the status of MMR genes–proteins (including MSI) in the relationship with ACC (adrenocortical carcinoma) according to current knowledge. This is a narrative review. We included PubMed-accessed, full-length English papers published between January 2012 and March 2023. We searched studies on ACC patients for whom MMR status was assessed, respectively subjects harboring MMR germline mutations, namely Lynch syndrome (LS), who were diagnosed with ACC. MMR system assessments in ACCs involve a low level of statistical evidence. Generally, there are two main types of endocrine insights: 1. the role of MMR status as a prognostic marker in different endocrine malignancies (including ACC)—which is the topic of the present work, and 2. establishing the indication of immune checkpoint inhibitors (ICPIs) in selective, mostly highly aggressive, non-responsive to standard care forms upon MMR evaluation (which belongs to the larger chapter of immunotherapy in ACCs). Our one-decade, sample-case study (which, to our knowledge, it is the most comprehensive of its kind) identified 11 original articles (from 1 patient to 634 subjects per study diagnosed with either ACC or LS). We identified four studies published in 2013 and 2020 and two in 2021, three cohorts and two retrospective studies (the publication from 2013 includes a retrospective and a cohort distinct section). Among these four studies, patients already confirmed to have LS (N = 643, respective 135) were found to be associated with ACC (N = 3, respective 2), resulting in a prevalence of 0.0046%, with a respective of 1.4% being confirmed (despite not having a large amount of similar data outside these two studies). Studies on ACC patients (N = 364, respective 36 pediatric individuals, and 94 subjects with ACC) showed that 13.7% had different MMR gene anomalies, with a respective of 8.57% (non-germline mutations), while 3.2% had MMR germline mutations (N = 3/94 cases). Two case series included one family, with a respective four persons with LS, and each article introduced one case with LS-ACC. Another five case reports (between 2018 and 2021) revealed an additional five subjects (one case per paper) diagnosed with LS and ACC (female to male ratio of 4 to 1; aged between 44 and 68). Interesting genetic testing involved children with TP53-positive ACC and further MMR anomalies or an MSH2 gene-positive subject with LS with a concurrent germline RET mutation. The first report of LS-ACC referred for PD-1 blockade was published in 2018. Nevertheless, the use of ICPI in ACCs (as similarly seen in metastatic pheochromocytoma) is still limited. Pan-cancer and multi-omics analysis in adults with ACC, in order to classify the candidates for immunotherapy, had heterogeneous results, and integrating an MMR system in this larger and challenging picture is still an open issue. Whether individuals diagnosed with LS should undergo surveillance for ACC has not yet been proven. An assessment of tumor-related MMR/MSI status in ACC might be helpful. Further algorithms for diagnostics and therapy, also taking into consideration innovative biomarkers as MMR-MSI, are necessary.